Antiulcerogenic activity of Scutia buxifolia on gastric ulcers induced by ethanol in rats - Aline Augusti Boligon; Robson Borba de Freitas; Thiele Faccim de Brum; Emily Pansera Waczuk; Cláudia Vargas Klimaczewski; Daiana Silva de Ávila; Margareth Linde Athayde; Liliane de Freitas Bauermann (Elsevier, 2014)
Gastric ulcers affect many people around the world and their development is a result of the imbalance between aggressive and protective factors in the gastric mucosa. Scutia buxifolia, commonly known as coronilha, has attracted the interest of the scientific community due to its pharmacological properties and its potential therapeutic applications. In this study, the preventive effects of the crude extract of Scutia buxifolia (ceSb) against gastric ulcer induced by 70% ethanol were evaluated in male Wistar rats. In addition, the composition of ceSb was clarified by high-performance liquid chromatography (HPLC). S. buxifolia extract (100, 200 and 400 mg/kg body weight) attenuated oxidative and histopathological features induced by ethanol. Moreover, all evaluated doses of ceSb caused significant (P<0.001 and P<0.0001) and dose-dependent increase in sulfhydryl groups (NPSH) levels, catalase (CAT) and superoxide dismutase (SOD) activities. Furthermore, the administration of ceSb reversed the increase in lipid peroxidation produced by ethanol. The protective effect of the extract could be attributed to antioxidant compounds present in the ceSb, such as flavonoids and phenolic acids, which were quantified by HPLC. Thus, an antioxidant effect of the extract leads to a protection on gastric tissue. These results indicate that S. buxifolia could have a beneficial role against ethanol toxicity by preventing oxidative stress and gastric tissue injury.